1999
DOI: 10.1046/j.1365-2672.1999.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of thermostability in thermolysin – analysis of subsite S2 mutant enzymes of thermolysin

Abstract: An aromatic amino acid at position 115 (tryptophan residue; subsite S2) in thermolysin is known to be essential for proteolytic activity of thermolysin. Mutant enzymes substituted by phenylalanine (W115F) and tyrosine (W115Y) at position 115 were expressed at similar levels as the wild type (WT) enzyme in Bacillus subtilis. The thermostability of the W115Y mutant enzyme was equal to that of the WT. However, that of the W115F mutant enzyme was significantly lower than the WT. Enzymatic kcat/Km values of W115F i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…We previously reported that heat inactivation of TLN at 90°C was mainly caused through autodegradation and identified Asp 126 -Gly 127 , Gly 154 -Leu 155 , Ser 204 -Met 205 and Asp 207 -Pro 208 as the autodegradation sites under existing calcium ions ( Fig. 1; Kubo et al 1999;Matsumiya et al 2004). Furthermore, after substitution of Leu 155 , which is located in a nonconserved region of TLN, with various amino acids (Ala, Ser, Phe and Gly producing L155A, L155S, L155F and L155G, respectively) by site-directed mutagenesis, the thermostability of the mutant TLN increased because of suppression of the autodegradation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We previously reported that heat inactivation of TLN at 90°C was mainly caused through autodegradation and identified Asp 126 -Gly 127 , Gly 154 -Leu 155 , Ser 204 -Met 205 and Asp 207 -Pro 208 as the autodegradation sites under existing calcium ions ( Fig. 1; Kubo et al 1999;Matsumiya et al 2004). Furthermore, after substitution of Leu 155 , which is located in a nonconserved region of TLN, with various amino acids (Ala, Ser, Phe and Gly producing L155A, L155S, L155F and L155G, respectively) by site-directed mutagenesis, the thermostability of the mutant TLN increased because of suppression of the autodegradation.…”
Section: Introductionmentioning
confidence: 95%
“…We previously reported that heat inactivation of TLN at 90°C was mainly caused through autodegradation and identified Asp 126 ‐Gly 127 , Gly 154 ‐Leu 155 , Ser 204 ‐Met 205 and Asp 207 ‐Pro 208 as the autodegradation sites under existing calcium ions (Fig. 1; Kubo et al. 1999; Matsumiya et al.…”
Section: Introductionmentioning
confidence: 99%
“…disulfide bonds and hydrophobic packing [1][2][3][4][5]. Stability has also been enhanced by suppressing autodegradation; for example, the stabilities of subtilisin J, rat chymotrypsin, and HIV protease were enhanced by deleting or changing amino acids at autodegradation sites [6][7][8].…”
mentioning
confidence: 99%